Correlação entre estrutura fractal do citoesqueleto e a viscoelasticidade de fibroblastos - Santos, Wallace Vale dos (2022)
Cells are units present in all living beings and are responsible for various activities, both structural and functional. Understanding how this unit behaves is of great importance given the number of diseases that affect its functioning and, consequently, the health status of a given population. The goal of this work is to systematically study the correlation between the structure of the filamentous actin network (f-actin) and the cells viscoelasticity. The study of the cytoskeleton structure will be carried out through the analysis of confocal microscopy images of fibroblasts (L929 lineage) fixed and treated with optical markers binded to f-actin filaments, while the viscoelastic properties of the cells are characterized by Atomic Force Microscopy. The cells are divided into two groups, healthy cells and cells treated with cytochalasin, whose effect is to depolymerize the f-actin network, modifying the cytoskeleton structure. The structural alterations of the cytoskeleton are determined by calculating the fractal dimension of confocal images of the cells cytoskeleton. The measured data show: (i) the main effect of the cytochalasin is observed in the alteration of the viscoelastic relaxation exponents. The fast exponent (alpha) slightly grows from 0.75 to 0.78, while the slow exponent (beta) grows strongly from 0.23 to 0.37. (ii) The cytochalasin start to depolimerize f-actin less than a minute after drug application, and its effect stabilizes around 5 minutes after application. After that, viscoelastic properties remain unaltered for at least 30 minutes. (iii) The drug continus to depolimerize the cytoskeleton at least until 30 minutes after application, and provoking a reduction if the fractal dimension. (iv) The fractal dimension exhibits a inversely proportional behavior with respect to cell fluidity. (v) The substrate where cells are cultivated exhibits an important effect in the structure of the cytoskeleton, including the depolimerization dynamics.